101 things you can do for our children's future - Louv, Richard (Anchor Books, 1994)
101 Things You Can Do for Our Children's Future is a call to action to parents - as well as seniors, nonparents, employers, teachers, and all Americans - that shows how to create a better life for children now. With strategies ranging from the traditional to the revolutionary - from simple techniques to create more family time to ways to weave a "super-extended family," from how to create family-friendly workplaces to making libraries and parks safe places for children